ELPWA and molasses additives for high moisture sorghum grain - J. Heidker; H. Ilg; K. Bolsen; Keith C. Behnke (Kansas Agricultural Experiment Station Research Reports, 1983)
ELPWA (a lactobacillus inoculant with antioxidant), molasses, or both combined were evaluated as additives to high moisture sorghum grain ensiled in concrete stave silos. ELPWA treated grain had the greatest temperature increase during ensiling. Final lactobacillus counts were higher in the ELPWA + molasses treated grain, however, the initial rate of increase was greatest in ELPWA or molasses treated grains. Control and molasses treated grains had the fastest decline in pH and the lowest final pH. Aerobic stability of the ensiled grain depended on the strata of the silo sampled and the temperature to which the grain was exposed but aerobically stability was adequate in all grains. Group-fed steers receiving control grain were more efficient (P<.05) than those receiving molasses + ELPWA treated grain. There were no significant differences among grain treatments for rates or efficiencies of gains for heifers or individually-fed steers.
Keywords: Cattlemen& #x27; s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Molasses; Sorghum grain; Stave silo